Cellulose fiber-based separator for electrochemical devices

KR103012552B1Active Publication Date: 2026-09-02DELFORTGROUP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020237014932
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-13
Filing Date
2021-10-11
Publication Date
2026-09-02
Estimated Expiration
2041-10-11

Smart Images

  • Figure 112023048656143-PCT00005_ABST
    Figure 112023048656143-PCT00005_ABST
Patent Text Reader

Abstract

A separator for an electrochemical device is presented, wherein at least 70% and up to 95% of the mass of the separator is formed by fibrillated fibers of regenerated cellulose, at least 3% and up to 30% of the mass of the separator is formed by cellulose having a high fine content, among the fibrillated fibers of regenerated cellulose having a length of at least 1 mm, at least 10% by number have a branched structure, and in the cellulose having a high fine content, the proportion of fibers having a length of less than 0.2 mm is at least 70% based on the sum of the lengths of the fibers in the cellulose having a high fine content.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a separator for an electrochemical device formed by a fiber substrate essentially composed of fibrillated fibers of regenerated cellulose and pulp having a high fine content. Such a separator has particularly advantageous properties, especially with respect to pore size distribution. Background Technology

[0002] An electrochemical device typically comprises at least an anode, a cathode, an electrolyte, a separator, a casing, and a current collector. The separator is impregnated with the electrolyte and serves the task of electrically separating the two electrodes. In this regard, it is also necessary to enable the flow of ions between the electrodes as unhindered as possible so that the electrochemical device may have advantageous characteristics, particularly fast charging and high current intake options.

[0003] These requirements for separators imply that they must be as thin as possible and possess high porosity so that the path of ions from one electrode to another through the pores of the separator is short and a high volume energy density of the electrochemical device is achieved. In particular, if the electrochemical device is a capacitor, porosity must be formed by a large number of small pores rather than a few large pores, because small pores can inhibit the growth of crystals, especially dendrites, on the electrodes. These crystals can short-circuit the capacitor and thus reduce its lifespan and performance. It is desirable to have as many small but uniformly sized pores as possible, that is, a pore size distribution with a small standard deviation.

[0004] In addition, the separator must be chemically stable with respect to the electrolyte, as the electrochemical device can be recharged multiple times and is typically used for several years. Therefore, the separator must also be stable in oxidation and reduction environments.

[0005] For safety reasons, the separator must also have excellent thermal stability to limit the risk of fire in the event of damage to the electrochemical element.

[0006] Finally, the separator requires sufficient mechanical strength to ensure that the electrochemical device can be manufactured without issues despite its minute thickness, and during manufacturing, it must absorb the electrolyte as quickly as possible into its entire pore volume to achieve high conductivity for ions.

[0007] According to the prior art, these numerical requirements can be met primarily by thin plastic films that can be manufactured with very uniform quality. However, the plastics used, typically polyolefins, are mostly thermoplastic and often not sufficiently thermally stable, which can lead to fire safety issues regarding electrochemical devices manufactured therefrom. This is mainly because the plastic shrinks at high temperatures and can no longer prevent large-scale contact between electrodes.

[0008] Attempts to use fibrous substrates as separators for electrochemical devices, particularly lithium-ion batteries, have so far been largely unsuccessful, as fibrous substrates of sufficient strength are often too thick, and due to raw materials and manufacturing processes, the pores are too large and the standard deviation of the pore size distribution is too high. Above all, separators made from cellulose fibers have proven difficult in this regard, even though cellulose fibers offer advantages in terms of safety, particularly dimensional stability at high temperatures, and ecology, because they are based on natural raw materials such as pulp fibers, which vary considerably in length, thickness, and shape.

[0009] Despite this unfavorable background, there is interest within the industry in making available separators for electrochemical devices that are essentially formed from cellulose fibers and possess properties favorable for use in electrochemical devices.

[0010] The object of the present invention is to provide a separator for an electrochemical device that is essentially formed from cellulose fibers and satisfies requirements regarding thickness, pore size distribution, strength, and chemical stability, thereby enabling the economically feasible utilization of safety and ecology-related benefits.

[0011] These objectives are achieved by the separator for an electrochemical device according to claim 1 and the method for manufacturing the separator for an electrochemical device according to claim 26. Further advantageous embodiments are provided in the dependent claims.

[0012] The inventors have discovered that the above objective can be achieved by a separator for an electrochemical device, wherein at least 70% and up to 95% of the mass of the separator is formed by fibrillated fibers of regenerated cellulose, at least 3% and up to 30% of the mass of the separator is formed by pulp having a high fine content, among the fibrillated fibers of regenerated cellulose having a length of at least 1 mm, at least 10% by number have a branched structure, and in the pulp having a high fine content, the proportion of fibers having a length of less than 0.2 mm is at least 70% of the total length of the fibers of the pulp having a high fine content.

[0013] A practical difficulty in the manufacture of fiber substrates containing micromaterials is to retain the micromaterials in the fiber substrate so that they are not lost during the manufacture of the fiber substrate and in subsequent process steps. This difficulty has been overcome by a special refining process provided by the inventors, which provides fibers of regenerated cellulose having a specific form. In this regard, the fibers of regenerated cellulose are primarily fibrillated and less cleaved, and a branched structure is created for at least a portion of the fibers, which, according to the inventors' findings, essentially contributes to retaining micromaterials within the fiber substrate. The branched structure is characterized primarily by the fibrils not being completely separated from one another, but still connected to a thicker fiber at one end. The branched structure is bonded to one another via hydrogen bonding, forms a network that contributes to high strength, and provides a basis for retaining additional fibers with branched structures. In this way, a sufficiently dense net capable of retaining micromaterials is created. In this regard, the micromaterials primarily serve to reduce pore size and create a pore size distribution with a small standard deviation.

[0014] Fibrillation of regenerated cellulose to produce a branched structure can be achieved particularly advantageously with a colloid mill.

[0015] In this regard, the fibers of the regenerated cellulose are micronized in such a way that some of the fibers have a branched structure. According to the present invention, at least 10% of all fibers of the fibrillated regenerated cellulose having a length of at least 1 mm have such a branched structure. Preferably, the proportion of fibers having a branched structure is higher, at least 15% each, and particularly preferably at least 20%, based on the number of fibers of the fibrillated regenerated cellulose having a length of at least 1 mm.

[0016] The separator according to the present invention is formed with at least 70% and up to 95%, preferably at least 75% and up to 90%, of the mass of the fibrillated fibers of the regenerated cellulose of the separator. This type and amount of fibers in the separator allows good strength to be obtained, so that the separator can also be processed into an electrochemical device.

[0017] The fibers of regenerated cellulose are preferably solvent-spun fibers, particularly preferably Lyocell® fibers.

[0018] The linear density of the fibers of the regenerated cellulose before fibrillation is important for fiber micronization. Preferably, the average linear density of the regenerated cellulose fibers is at least 0.8 g / 10000 m (0.8 dtex) and up to 3.0 g / 10000 m (3.0 dtex), particularly preferably at least 1.0 g / 10000 m (1.0 dtex) and up to 2.5 g / 10000 m (2.5 dtex).

[0019] The length of the fibers of the regenerated cellulose before fibrillation is primarily important for the strength of the separator, where longer fibers lead to higher strength but also imply higher energy consumption during micronization. Preferably, the average length of the fibers of the regenerated cellulose before fibrillation is at least 2 mm and at most 8 mm, particularly preferably at least 3 mm and at most 6 mm.

[0020] The separator according to the present invention is formed by pulp having a high fine content of at least 3% and up to 30%, preferably at least 5% and up to 20%, based on the mass of the separator. Pulp with a high fine content produces a pore size distribution with a small standard deviation at high porosity. A higher proportion of pulp with a high fine content makes dewatering the fiber web more difficult during the manufacture of the separator on a paper machine. Additionally, pulp with a high fine content is relatively difficult and expensive to manufacture. Thus, the specified interval provides a particularly advantageous combination of porosity, strength, cost, and dewatering time. Fibrillation of the fibers of regenerated cellulose also causes fines to form, which can be present in the separator in much larger quantities than the fines of the pulp with a high fine content. However, according to the inventors' findings, the fines of regenerated cellulose have a coarser structure and are therefore not suitable for obtaining high porosity with a low average pore size and a small standard deviation of the pore size distribution. On the other hand, the fines of pulp having a high fine content have a finer structure, and thus allow the average pore size and the standard deviation of the pore size distribution to be reduced much more effectively, even with a lower total content in the separator. In addition, since stronger fibrillation of regenerated cellulose fibers can hardly increase the proportion of fines without destroying fibers having a branched structure, in the context of the present invention, the proportion of fines is adjusted by adding fines from pulp having a high fine content.

[0021] According to the present invention, pulp having a high fine content is produced from pulp, wherein the pulp is preferably supplied from softwood, deciduous wood, or other plants, such as hemp, flax, jute, ramie, kenaf, kapok, coconut, abaca, sisal, bamboo, cotton, or esparto grass, or from recycled pulp. Additionally, a mixture of pulps of different origins may be used to produce pulp having a high fine content. Particularly preferably, the pulp is supplied from deciduous wood or softwood.

[0022] According to the present invention, a pulp having a high fine content is characterized in that the proportion of pulp fibers having a length of less than 0.2 mm is at least 70% of the total length of the pulp fibers. This means that the sum of the lengths of all pulp fibers having a length of less than 0.2 mm is at least 70% of the sum of the lengths of all pulp fibers within the pulp having a high fine content. Fines contribute to further reducing the pore size and creating a pore size distribution with a small standard deviation at high porosity. Accordingly, preferably, the fine content within the pulp having a high fine content is higher such that the proportion of pulp fibers having a length of less than 0.2 mm is at least 80%, particularly preferably at least 90%, of the total length of the pulp fibers within the pulp having a high fine content. Such fine content can be determined by an image analysis method according to ISO 16065-2:2014.

[0023] Nano-fibrillated pulp or micro-fibrillated pulp can be very suitable as a pulp with a high fine matter content and is commercially available, for example, from Borregaard under the trade name Exilva-F-01.

[0024] In a preferred embodiment, the characteristics of the separator can be further improved to produce much shorter and finer fibers by more precisely adjusting the length and thickness of the fines during the manufacturing process of pulp having a high fine content, which is known as secondary fines. Secondary fines are fibers having a length of less than 100 μm and a thickness D (μm) satisfying the following inequality.

[0025] D ≤ 50 - 0.3·L,

[0026] Here, L is substituted with μm. Preferably, the proportion of secondary fines in the pulp having a high fine content is at least 40%, particularly preferably at least 60%, with respect to the total length of the fiber in the pulp having a high fine content. The proportion of secondary fines can also be determined by an image analysis method according to ISO 16065-2:2014. As an example, the L&W Fiber Tester Plus measuring instrument from Lorentzen & Wettre can be used to determine the fiber length, fiber thickness, and their distribution.

[0027] The separator according to the present invention may contain additional components suitable for the manufacturing method, which a person skilled in the art may select based on experience; these include, for example, polyvinyl alcohol, polyethylene glycol, polyvinylidene fluoride, guarana, starch, carboxymethyl cellulose, methylcellulose, dialdehyde, e.g., glyoxal, and inorganic fillers, e.g., kaolin, titanium dioxide (TiO2), silicon dioxide (SiO2), aluminum oxide (Al2O3), zirconium dioxide (ZrO2), or calcium carbonate (CaCO3).

[0028] In addition to fibrillated fibers of regenerated cellulose and pulp having a high fine content, the separator according to the present invention may also contain additional fibers. These may include, for example, fibers from cellulose derivatives, non-fibrillated fibers from regenerated cellulose, glass fibers, plastic fibers, e.g., fibers from polyolefins, e.g., polyethylene or polypropylene; fibers from polyesters, e.g., polyethylene terephthalate or polylactic acid; fibers from polyethers, polysulfones, polyurethanes, polyamides, polyimides, polyvinyl alcohols, polyacrylonitrile, polyphenylene sulfides, or fibers from ethylene-vinyl acetate copolymers.

[0029] However, preferably, the total proportion of other fibers is up to 10% of the mass of the separator, particularly preferably up to 5%.

[0030] The separator according to the present invention must be thin so that ions flowing in the electrolyte need to cover only a short path through the pores of the separator between two electrodes, and so that the electrochemical device manufactured therefrom has a high volume energy density. On the other hand, a specific thickness is required to electrically isolate the electrodes safely from each other and to achieve excellent strength in the separator. Accordingly, preferably, the thickness of the separator according to the present invention is at least 10 μm and up to 55 μm, particularly preferably at least 12 μm and up to 35 μm. The thickness of the separator can be determined for a single sheet according to ISO 534:2011.

[0031] The basis weight of the separator provides excellent strength, but the thickness and material consumption increase with the basis weight. Therefore, preferably, the basis weight of the separator according to the present invention is at least 8 g / m² 2 and up to 30 g / m² 2 , particularly preferably at least 12 g / m² 2 and up to 25 g / m²2 The basis weight can be determined according to ISO 536:2012.

[0032] The porosity of a separator is the ratio of the pore volume to the total volume of the separator, and is typically expressed as a percentage. The porosity of the separator can be estimated from the thickness and basis weight determined according to ISO 534:2011, and the fiber density, where 1500 kg / m³ 3 The density of the fibers can be selected. Using these assumptions, the porosity μ can be roughly calculated as the ratio of the pore volume to the total volume of the separator.

[0033]

[0034] Here, m is the basis weight (g / m²) 2 ) and d is the thickness (μm), and the porosity is obtained as a value from 0 to 1 and can be converted into a percentage by multiplying by 100. The porosity should be as high as possible, but is limited from the above by the requirements that the mechanical strength and pores should be as small as possible, which are mainly required. Preferably, the porosity is at least 30% and at most 85%, particularly preferably at least 35% and at most 75%.

[0035] The pore size distribution, mean flow pore size, and standard deviation of the mean flow pore size can be determined by capillary flow pore measurement according to the literature [ASTM F316-03(2019) Standard Test Methods for Pore Size Characteristics of Membrane Filters by Bubble Point and Mean Flow Pore Test]. In this regard, the amount of medium flowing through the separator is determined as the pressure difference increases. This measurement method is particularly suitable for separators because the separator detects only the pores that pass through it, and the narrowest point of each pore determines the flow. This characteristic of the pores is also important for the conduction of ions through the separator.

[0036] The pores within the separator must not exceed a specific size to limit the growth of dendrites on the electrodes, and they must all be of the same size, that is, have a pore size distribution with a small standard deviation. Accordingly, preferably, the average flow pore size is at least 40 nm and up to 1000 nm, preferably at least 50 nm and up to 800 nm.

[0037] Typically, the pore size within the separator according to the present invention is unimode distributed, so the width of the pore size distribution can be well characterized by the standard deviation of the average flow pore size. Accordingly, for the separator according to the present invention, the standard deviation of the average flow pore size is preferably at least 3 nm and up to 200 nm, particularly preferably at least 3 nm and up to 100 nm. Alternatively or in a complementary manner to the standard deviation of the average flow pore size, the pore size distribution is also the flow pore size D 90 It can be characterized by, where 90% of the flow through the pore is, and the flow pore size is D 90D to occur through crafting that does not exceed the value 90 This is determined. Flow work size D 90 The is preferably at least 100 nm and up to 1500 nm, particularly preferably at least 200 nm and up to 1000 nm.

[0038] The strength of the separator is important for processing the separator into an electrochemical device. Strength can be characterized by tensile strength and can be determined according to ISO 1924-2:2008. Due to the manufacturing type and fibers having a branched structure, the tensile strength does not depend particularly strongly on the direction in which the sample is taken from the separator. Therefore, if the requirement is met in at least one direction, it is considered that the requirement is satisfied. The tensile strength of the separator according to the present invention is at least 0.3 kN / m and at most 2 kN / m, particularly preferably at least 0.5 kN / m and at most 1.5 kN / m. Strength can be increased by stronger micronization of the fibers of the regenerated cellulose; however, this implies higher energy consumption, which further shortens the fibers, thereby preventing the strength from being increased arbitrarily.

[0039] When automatically processing a separator into an electrochemical element, the elongation of the separator is important. Elongation can be described by the elongation at break and can be determined according to ISO 1924-2:2008. As with tensile strength, the elongation at break also depends on the direction in which the sample is taken from the separator. However, since this dependence is not very pronounced, the requirement is satisfied if it is met in at least one direction. The elongation at break of the separator according to the present invention is preferably at least 0.5% and at most 4.0%, particularly preferably at least 1.0% and at most 3.5%.

[0040] The elasticity of the separator is also important. This can be characterized by the elastic modulus derived from the measurement of the force-deformation curve according to ISO 1924-2:2008. In the case of the separator according to the present invention, since the elastic modulus also depends only slightly on the direction in which the sample is taken from the separator, the elastic modulus regardless of direction is preferably at least 1 GPa and at most 8 GPa, particularly preferably at least 2 GPa and at most 6 GPa.

[0041] Because measuring the pore size distribution by capillary flow porosimetry is complex, the pore structure of a separator can be characterized in a simplified manner by air permeability according to Gurley. Air permeability is also an excellent indicator of how quickly a separator can absorb an electrolyte. When manufacturing electrochemical devices, a high absorption rate is advantageous for fabrication. Air permeability according to Gurley can be determined according to ISO 5636-5:2013, preferably at least 10 s and up to 450 s, preferably at least 40 s and up to 300 s.

[0042] A separator can be used in an electrochemical device. An electrochemical device according to the present invention comprises two electrodes, an electrolyte, and a separator according to the present invention. Preferably, the electrochemical device is a capacitor, a hybrid capacitor, a supercapacitor, or a capacitor, and particularly preferably, the electrochemical device is a lithium-ion battery.

[0043] A separator according to the present invention can be manufactured by the following method according to the present invention, comprising the following steps:

[0044] A - Step of preparing an aqueous suspension of fibers of regenerated cellulose that can be fibrillated,

[0045] B - Step of fibrillating the fibers of the regenerated cellulose from Step A,

[0046] C - Step of adding an aqueous suspension of fibrillated fibers of regenerated cellulose from Step B to a head box,

[0047] D - A step of forming a fiber web by applying an aqueous suspension from step C to a progressing wire,

[0048] E - Step of dewatering the fiber web on the progress wire,

[0049] F - Step of drying the fiber web in the first drying device,

[0050] G - Step of drying the fiber web in the second drying device,

[0051] H - Step of winding a separator formed by a fiber web,

[0052] Here, among the fibers of the regenerated cellulose in step C having a length of at least 1 mm, at least 10% of the fibers are fibrillated to have a branched structure based on the number of fibers, and

[0053] Here, the pulp having a high fine matter content is in at least one of the following steps

[0054] (a) In step A, by adding to the aqueous suspension,

[0055] (b) In step C, by adding to the head box,

[0056] (c) In step D, by applying to the fiber web formed on the progress wire from the additional head box,

[0057] (d) Between steps E and F, by applying to the fiber web in the application device, or

[0058] (e) Between steps G and H, added by applying to the fiber web in the application device, and

[0059] Here, in a pulp having a high fine material content, at least 70% of the fibers have a length of less than 0.2 mm relative to the total length of the fibers,

[0060] Here, at least 70% and up to 95% of the mass of the separator after drying in step G is formed by fibrillated fibers of regenerated cellulose, and at least 3% and up to 30% of the mass of the separator is formed by pulp having a high fine content.

[0061] In a preferred embodiment of the method according to the present invention, step B is performed such that the fibers of the regenerated cellulose are more fibrillated and less cut, and particularly preferably, step B is performed in a colloid mill. The inventors have discovered that the formation of a branched structure depends less on the cutting of the fibers, and that a significant portion of the fibrillation is caused by fiber-fiber friction. Although this type of fibrillation can be performed in various microfabrication devices, a colloid mill has proven to be particularly suitable.

[0062] In a preferred embodiment, step B is performed such that the fineness according to the Schopper Riegler (°SR), measured according to ISO 5267-1:1999, is at least 70 °SR and up to 100 °SR, particularly preferably at least 80 °SR and up to 95 °SR. Thus, stronger fineness, and a higher degree of fineness according to the Schopper Riegler, leads to more fibrils, higher strength, and a finer pore structure. Since energy consumption is significant and the fiber shortens with increasing fineness, the specified interval is a favorable compromise.

[0063] By micronizing the regenerated cellulose in step B, fibers having a length of less than 0.2 mm can be produced, but the proportion should not be very high because the fibers of the regenerated cellulose must mainly form a network containing fibers of pulp having a high fineness content. Accordingly, preferably, in the fibrillated fibers of the regenerated cellulose after step B, step B is performed such that at least 30% and up to 70% of the total fiber length, particularly preferably at least 40% and up to 65%, are formed by fibers having a length of less than 0.2 mm. This proportion of fibers having a length of less than 0.2 mm can be determined according to ISO 16065-2:2014.

[0064] In a preferred embodiment of the method according to the present invention, at least steps C to G are performed in a paper machine.

[0065] The drying devices of steps F and G may be different or the same, and preferably may be formed by one or more heated drying cylinders.

[0066] In a preferred embodiment of the method according to the present invention, the fiber web may be calendered between steps G and H. In this regard, the fiber web passes through at least one nip, where mechanical pressure is applied to the fiber web. Particularly preferably, the number of nips through which the fiber web passes is at least 2 and up to 14, particularly preferably at least 5 and up to 10. The line load applied to the fiber web at all or at least some of the nips is preferably at least 20 kN / m and up to 600 kN / m, preferably at least 60 kN / m and up to 400 kN / m. Calendering helps to reduce the thickness of the separator and compress the structure to create smaller pores. When step (e) is performed, calendering is preferably performed between step (e) and step H.

[0067] In a preferred embodiment of the method according to the present invention, the application of at least a portion of the pulp having a high fine content is performed by a film press or coating device in step (d).

[0068] In a preferred embodiment of the method according to the present invention, the application of at least a portion of the pulp having a high fine content is performed by printing or spraying in step (e). In this preferred embodiment, the application of the pulp having a high fine content may be performed in one or both, and in particular in both.

[0069] The separator from step H of the method according to the present invention is preferably formed by fibrillated fibers of regenerated cellulose, comprising at least 75% and up to 90% of the mass of the separator.

[0070] The fibrillated fiber of regenerated cellulose from step A of the method according to the present invention is preferably a solvent-spun fiber, particularly preferably a lyocell® fiber.

[0071] In step A of the method according to the present invention, the average length of the fibrillated fibers of the regenerated cellulose is at least 2 mm and at most 8 mm, particularly preferably at least 3 mm and at most 6 mm. The average length of the fibers can be determined according to ISO 16065-2:2014.

[0072] The separator of step H of the method according to the present invention is preferably formed by pulp having a high fine content of at least 5% and up to 20% based on the mass of the separator.

[0073] According to the present invention, the pulp having a high fine content added in at least one of steps (a) to (e) is preferably produced from pulp supplied from coniferous wood, deciduous wood, or other plants, such as hemp, flax, jute, ramie, kenaf, kapok, coconut, abaca, sisal bamboo, cotton, or esparto grass, or from recycled pulp. Additionally, a mixture of pulps from different sources may be used to produce the pulp having a high fine content. Particularly preferably, the pulp is supplied from coniferous wood or deciduous wood.

[0074] According to the present invention, a pulp having a high fine content from at least one of steps (a) to (e) is characterized in that the proportion of fibers having a length of less than 0.2 mm is at least 70% of the total length of fibers in the pulp having a high fine content. Preferably, the proportion of fibers having a length of less than 0.2 mm is at least 80%, particularly preferably at least 90%, of the total length of fibers in the pulp having a high fine content. The content of such fines can be determined by an image analysis method according to ISO 16065-2:2014.

[0075] The pulp having a high fine content from at least one of steps (a) to (e) may preferably contain secondary fines. The secondary fines are fibers having a length of less than 100 μm and a thickness D (μm) satisfying the following inequality.

[0076] D ≤ 50 - 0.3·L,

[0077] Here, L is substituted with μm. Preferably, the proportion of secondary fines in the pulp having a high fine content is at least 40%, particularly preferably at least 60%, with respect to the total length of the fibers in the pulp having a high fine content. The proportion of secondary fines can also be determined by an image analysis method according to ISO 16065-2:2014. Brief explanation of the drawing

[0078] FIG. 1 shows examples of fibrillated fibers of regenerated cellulose having a branched structure after dissolving a separator according to the present invention in water, as shown in FIG. 1a to 1i. FIG. 2 shows examples of fibrillated fibers of regenerated cellulose having a branched structure at the torn edge of a separator according to the present invention, as shown in FIG. 2a to 2c, through images obtained by an optical microscope. Figure 3 shows examples of fibrillated fibers of regenerated cellulose that do not have a branched structure, as shown in Figures 3a and 3b. Specific details for implementing the invention

[0079] Some preferred embodiments of the separator according to the present invention and the method according to the present invention, as well as a separator not according to the present invention as a comparative example, will be described below.

[0080] An aqueous suspension of 4 mm-length fibrillated fibers (Lyocell®) of regenerated cellulose having 1.7 dtex was prepared (Step A) and micronized in a colloid mill to a fineness of 82°SR or 93°SR, respectively, when measured according to ISO 5267-1:1999. Subsequently, the suspension was transported to a headbox (Step C), whereby pulp with a high fineness content was added to the headbox (Step B). Subsequently, a fiber web was formed on a paper machine according to Steps D through H, dried, and wound.

[0081] The amounts of fibers of regenerated cellulose and pulp having a high fine content were selected so that the separator is formed by 85% to 100% fibers of regenerated cellulose and 0%, 10%, or 15% of pulp having a high fine content, where the percentages are based on the mass of the final dried separator. In total, three separators according to the present invention (S1, S2, and S3) and two separators not according to the present invention (P1 and P2) were manufactured, a fourth separator according to the present invention (S4) by calendering S1, and an additional separator not according to the present invention (P3) by calendering P1 were manufactured. The characteristics of S1, S2, S3, S4 and P1, P2, P3 are summarized in Tables 1 and 2, where Table 1 provides the mass of the lyocell fiber, the mass of the high fine content pulp (HFP), fineness (DR), basis weight (BW), thickness (TH), tensile strength in the machine direction (TS-MD), and elastic modulus in the machine direction (MoE-MD), and Table 1 provides the porosity (PV), air permeability (AP), mean flow pore size (M-PS), standard deviation of mean flow pore size (SD-PS), and flow pore size D as defined above for the same separator. 90 (90%-PS) is shown in Table 2.

[0082] Table 1

[0083]

[0084] Table 2

[0085]

[0086] Air permeability (AP) can serve as a measure of porosity, and it can be seen that separators S1 and S2 according to the present invention, and S3, compared to P1 and S2, respectively, have significantly lower air permeability at equivalent porosity, i.e., higher values ​​according to Gurley. This indicates that the average flow pore size is lower in the separators according to the present invention, and for this reason, these separators are more suitable for use in electrochemical devices than separators not according to the present invention.

[0087] In particular, separator P2 not according to the present invention has a very high air permeability, that is, a low value according to Gulli, and thus has large pores, and for this reason, in an electrochemical device, particularly in a lithium-ion battery having this separator, over time, dendrites may form starting from the electrode, which poses a risk of reducing the lifespan and performance of the electrochemical device.

[0088] A comparison of separators S1, S2, and S3 according to the present invention with separators P1 and P2 not according to the present invention, which do not have pulp with a high fine content, also shows the positive effect of pulp with a high fine content on the strength of the separators.

[0089] The pore size distribution of separators S1 and P1 was determined by the capillary flow pore measurement method according to the literature [Standard Test Method for Pore Size Characteristics of Membrane Filters by Bubble Point and Mean Flow Pore Test ASTM F316-03(2019)].

[0090] In the case of S1, an average flow pore size of 175 nm was found with a standard deviation of an average flow pore size of about 108 nm, whereas separator P1, which is not according to the present invention, had an average flow pore size of 275 nm with a standard deviation of an average flow pore size of about 146 nm. Therefore, in separator S2 according to the present invention, pulp having a high fine content induces a pore size distribution with a smaller average flow pore size and a smaller standard deviation, both of which are advantageous for the characteristics of electrochemical devices manufactured therefrom.

[0091] FIGS. 1a to 1i illustrate examples of fibrillated fibers of regenerated cellulose having a length of at least 1 mm and a branched structure, wherein in FIGS. 1a to 1i, the same number refers to similar objects. In this regard, a separator according to the present invention was dissolved in water, and an image of the fiber was obtained using the L&W Fiber Tester Plus of Lorentzen & Wettre. The branched structure is characterized by multiple fibrils (12) being bonded to the fiber (11) to form branches of the fiber (11). Additionally, fibrils (13) that were no longer bonded to the fiber (11) were also present. The length (14) of FIGS. 1a to 1i is 1 mm, and the fiber (11) is longer than 1 mm. FIGS. 1a to 1i are provided merely as examples, and the fibrillated fibers of regenerated cellulose may also have substantially different shapes, provided that essential elements (11 and 12) of a branched structure are present and the fibers have a length of at least 1 mm when they occur in a separator according to the present invention.

[0092] FIGS. 2a to 2c illustrate examples of fibrillated fibers of regenerated cellulose having a length of at least 1 mm and a branched structure, wherein in FIGS. 2a to 2c, the same number also indicates a similar object. In this regard, a separator according to the present invention was torn into two parts, and an image of the fiber was obtained from the torn edge using an optical microscope. The branched structure is characterized by multiple fibrils (22) being bonded to the fiber (21) to form branches of the fiber (21). Each of FIGS. 2a to 2c shows a length (24) of 200 μm and a fiber (21) longer than 1 mm. FIGS. 2a to 2c are also provided merely as examples, and the fibrillated fibers of regenerated cellulose occurring in the separator according to the present invention may also have substantially different shapes as long as the essential elements (21 and 22) of the branched structure are present and the fiber has a length of at least 1 mm.

[0093] FIGS. 3a and 3b illustrate, for example, fibrillated fibers of regenerated cellulose that do not have a branched structure. Additionally, images were acquired using the L&W Fiber Tester Plus from Lorenzen & Wetre. In FIGS. 3a and 3b, the length (34) is 500 μm. In FIG. 3a, for example, fibrillated fibers (35) are shown, which are produced by micronizing regenerated cellulose, where micronization primarily results in shortening of the fibers. These fibers do not exhibit a branched structure because the fibrils are not sufficiently released from the fibers (35). The fibers (35) do not form a network that is rigid enough to retain microparticles within the fiber network.

[0094] In FIG. 3b, fibrillated fibers (36) are shown as examples produced by strong micronization of regenerated cellulose, where micronization resulted in the complete separation of fibrils from the fibers. The fibrillated fibers (36) also do not exhibit a branched structure and are therefore not suitable for forming a sufficiently dense fiber network.

[0095] From FIGS. 1 to 3, it can be seen that fiber micronization is very important for fiber morphology, and that fibers having a branched structure and a length of at least 1 mm can be obtained in sufficient quantities only by selecting an appropriate micronization method, such as in a colloid mill, for example, as shown in FIGS. 1 and 2.

[0096] Separator (S1) according to the present invention and separator (P1) not according to the present invention were further calendered with a calender having 8 nips with a line load of 150 kN / m, thereby obtaining an additional separator (S4) according to the present invention from S1 and a separator (P3) not according to the present invention from P1. The pore size distribution of separators S4 and P3 was determined by capillary flow porosimetry. A comparison of S1 and S4 and a comparison of P1 and P3 indicate that, by calendering, the average flow pore size can be reduced, and at the same time, the air permeability is also reduced.

[0097] A lithium-ion battery was manufactured from separators S1, S2, and S3 according to the present invention, and the main functions were verified so that the separators are suitable for use in lithium-ion batteries or other electrochemical devices in any case.

[0098] In addition, separators P1 and P2 that do not conform to the present invention are, in principle, suitable for lithium-ion batteries or other electrochemical devices, but their characteristics are not as superior as those of the separator according to the present invention.

Claims

Claim 1 A separator for an electrochemical device, wherein at least 70% and up to 95% of the mass of the separator is formed by fibrillated fibers of regenerated cellulose, and at least 3% and up to 30% of the mass of the separator is formed by pulp having a high fine content, wherein in the pulp having a high fine content, the proportion of fibers having a length of less than 0.2 mm is at least 70% of the total length of the fibers of the pulp having a high fine content, and wherein, among the fibrillated fibers of regenerated cellulose having a length of at least 1 mm, at least 10% by number have a branched structure, and the separator is free of plastic fibers or contains less than 5% of the mass of the separator. Claim 2 A separator for an electrochemical device according to claim 1, wherein at least 20% of the fibrillated fibers of regenerated cellulose having a length of at least 1 mm have a branched structure based on the number. Claim 3 A separator for an electrochemical device according to claim 1 or 2, wherein at least 75% and up to 90% of the separator is formed from fibrillated fibers of regenerated cellulose with respect to the mass of the separator. Claim 4 A separator for an electrochemical device according to claim 1 or 2, wherein the average linear density of the fibers of the regenerated cellulose prior to fibrillation is at least 0.8 g / 10000 m (0.8 dtex) and at most 3.0 g / 10000 m (3.0 dtex). Claim 5 A separator for an electrochemical device according to claim 1 or 2, wherein the average length of the fibers of the regenerated cellulose before fibrillation is at least 2 mm and at most 8 mm. Claim 6 A separator for an electrochemical device formed by pulp having a high fine content of at least 5% and up to 20% with respect to the mass of the separator, in accordance with claim 1 or 2. Claim 7 A separator for an electrochemical device according to claim 1 or 2, wherein the proportion of pulp fibers having a length of less than 0.2 mm is at least 80% of the total length of the pulp fibers having a high fine content. Claim 8 A separator for an electrochemical device according to claim 1 or 2, wherein the pulp having a high fine matter content is formed by nano-fibrillated pulp or micro-fibrillated pulp. Claim 9 A separator for an electrochemical device according to claim 1 or 2, wherein the pulp having a high fine content contains secondary fines formed by fibers having a length L (μm) of less than 100 and a thickness D (μm) satisfying the following inequality, D ≤ 50 - 0.3·L, wherein the ratio of secondary fines in the pulp having a high fine content is at least 40% with respect to the total length of the fibers of the pulp having a high fine content. Claim 10 A separator for an electrochemical device according to claim 1 or 2, comprising, in addition to the fibrillated fibers of the regenerated cellulose and the pulp having a high fine content, additional fibers selected from the group consisting of fibers from cellulose derivatives, non-fibrillated fibers from regenerated cellulose, glass fibers, and plastic fibers. Claim 11 A separator for an electrochemical device according to claim 1 or 2, wherein the thickness of the separator determined for a single sheet according to ISO 534:2011 is at least 12 μm and at most 35 μm. Claim 12 In claim 1 or 2, the basis weight of the separator determined according to ISO 536:2012 is at least 12 g / m² 2 and up to 25 g / m² 2 Separator for electrochemical devices. Claim 13 A separator for an electrochemical device according to claim 1 or 2, wherein the average flow pore size of the separator, measured by capillary flow porosimetry according to ASTM F316-03 (2019), is at least 50 nm and up to 800 nm. Claim 14 A separator for an electrochemical device according to claim 1 or 2, wherein the standard deviation of the average flow pore size measured according to ASTM F316-03 (2019) is at least 3 nm and at most 200 nm. Claim 15 In claim 1 or 2, D for a distribution of flow pore sizes of at least 100 nm and up to 1500 nm. 90 It has a value, where D 90 90% of the silver flow is, the flow pore size is D 90 A separator for an electrochemical device that is determined to pass through a pore that does not exceed a value. Claim 16 A separator for an electrochemical device according to claim 1 or 2, wherein the elastic modulus of the separator determined by the measurement of the force-strain curve in at least one direction according to ISO 1924-2:2008 is at least 1 GPa and up to 8 GPa. Claim 17 A separator for an electrochemical device according to claim 1 or 2, wherein the air permeability according to Gurley of the separator, as determined according to ISO 5636-5:2013, is at least 10 s and at most 450 s. Claim 18 An electrochemical device comprising two electrodes, an electrolyte, and a separator according to claim 1 or 2. Claim 19 In paragraph 18, an electrochemical element formed by a capacitor, a hybrid capacitor, a supercapacitor, or a capacitor. Claim 20 A method for manufacturing a separator for an electrochemical device comprising the following steps: A - preparing an aqueous suspension of fibers of regenerated cellulose capable of fibrillation; B - fibrillating the fibers of regenerated cellulose from step A; C - adding the aqueous suspension of fibrillated fibers of regenerated cellulose from step B to a head box; D - applying the aqueous suspension from step C to a lead wire to form a fiber web; E - dewatering the fiber web on the lead wire; F - drying the fiber web in a first drying device; G - drying the fiber web in a second drying device; H - winding the separator formed by the fiber web, wherein the fibers of regenerated cellulose in step C are fibers having a length of at least 1 mm, wherein at least 10% of the fibers are fibrillated based on the number of fibers to have a branched structure, and wherein a pulp having a high fine content is added to the aqueous suspension in at least one of the following steps (a) in step A, by adding to the aqueous suspension, and (b) in step B, A method of manufacturing in which, by adding to a head box, (c) by applying to a fiber web formed on a progress wire from an additional head box in step D, (d) by applying to a fiber web in an application device between steps E and F, or (e) by applying to a fiber web in an application device between steps G and H, wherein, in a pulp having a high fine content, at least 70% of the fibers have a length of less than 0.2 mm relative to the total length of the fibers, and at least 70% and up to 95% of the mass of the separator after drying in step G is formed by fibrillated fibers of regenerated cellulose, and at least 3% and up to 30% of the mass of the separator is formed by a pulp having a high fine content, and the separator after drying in step G is free of plastic fibers or contains an amount of plastic fibers less than 5% of the mass of the separator, and wherein step B is performed in a colloid mill. Claim 21 A manufacturing method according to claim 20, wherein step B is performed such that in the fibrillated fibers of the regenerated cellulose after step B, at least 30% and up to 70% of the total length of the fibers are formed by fibers having a length of less than 0.2 mm. Claim 22 A manufacturing method according to claim 20 or 21, wherein the fiber web is calendered between steps G and H. Claim 23 A manufacturing method according to claim 22, wherein a fiber web passes through at least one nip, or at least two and up to fourteen nips, and mechanical pressure is applied to the fiber web. Claim 24 A manufacturing method according to claim 23, wherein the line load applied to the fiber web at least in part of the nip is at least 20 kN / m and up to 600 kN / m. Claim 25 A manufacturing method according to claim 22, wherein calendering is performed between step (e) and H. Claim 26 A manufacturing method according to claim 20 or 21, wherein at least a portion of the pulp having a high fine content in step (d) is applied by a film press or a coating device. Claim 27 A manufacturing method according to claim 20 or 21, wherein at least a portion of the application of the pulp having a high fine content in step (e) is performed by printing or spraying, wherein the application of the pulp having a high fine content is performed on both sides. Claim 28 A method of manufacturing according to claim 20 or 21, wherein the separator from step H is formed by fibrillated fibers of regenerated cellulose comprising at least 75% and up to 90% of the mass of the separator. Claim 29 A method of manufacturing according to claim 20 or 21, wherein the average length of the fibrillated fibers of the regenerated cellulose in step A is at least 2 mm and at most 8 mm. Claim 30 A manufacturing method according to claim 20 or 21, wherein the separator from step H is formed by pulp having a high fine content of at least 5% and up to 20% with respect to the mass of the separator. Claim 31 A method of manufacturing according to claim 20 or 21, wherein, for a pulp having a high fine content from at least one of steps (a) to (e), the ratio of fibers having a length of less than 0.2 mm is at least 80% of the total length of fibers in the pulp having a high fine content. Claim 32 A method of manufacturing according to claim 20 or 21, wherein a pulp having a high fine content from at least one of steps (a) to (e) contains secondary fines formed by fibers having a length L (μm) of less than 100 and a thickness D (μm) satisfying the following inequality, D ≤ 50 - 0.3·L, wherein the ratio of secondary fines in the pulp having a high fine content is at least 40% with respect to the total length of the fibers in the pulp having a high fine content. Claim 33 delete Claim 34 delete Claim 35 delete Claim 36 delete Claim 37 delete Claim 38 delete Claim 39 delete Claim 40 delete Claim 41 delete Claim 42 delete Claim 43 delete

Citation Information

Patent Citations

  • Separator for lithium ion secondary battery and lithium ion secondary battery using the same

    JP2015162281A

  • Lithium ion secondary battery separator and lithium ion secondary battery arranged by use thereof

    JP2016171048A